More Than 50 Years after Its Discovery in SiO2 Octahedral Coordination Has Also Been Established in SiS2 at High Pressure - Evers, Jürgen; Möckl, Leonhard; Oehlinger, Gilbert; Köppe, Ralf; Schnöckel, Hansgeorg; Barkalov, Oleg; Medvedev, Sergey; Naumov, Pavel (Inorganic Chemistry, 2017)
SiO2 exhibits a high-pressure-high-temperature polymorphism, leading to an increase in silicon coordination number and density. However, for the related compound SiS2 such pressure-induced behavior has not been observed with tetrahedral coordination yet. All four crystal structures of SiS2 known so far contain silicon with tetrahedral coordination. In the orthorhombic, ambient-pressure phase these tetrahedra share edges and achieve only low space filling and density. Up to 4 GPa and 1473 K, three phases can be quenched as metastable phases from high-pressure high-temperature to ambient conditions. Space occupancy and density are increased first by edge and corner sharing and then by corner sharing alone. The structural situation of SiS2 up to the current study resembles that of SiO2 in 1960: Then, in its polymorphs only Si-O4 tetrahedra were known. But in 1961, a polymorph with rutile structure was discovered: octahedral Si-O6 coordination was established. Now, 50 years later, we report here on the transition from 4-fold to 6-fold coordination in SiS2, the sulfur analogue of silica.
CRIS-Team Scopus Importer:2024-09-09